Mitigating Agri-Business Risk Through Weather Derivatives - Patni, Vivek (Indian Journal of Finance, 2008)
The agri-business sector in India is largely dependent on monsoons. The arrival of monsoon remains uncertain and fate of millions of farmers lay in risk. In the first section, we examine the correlation between rainfall and food grain production in India. We also introduce the concept of weather derivatives. In the second section, we examine weather derivatives as a tool for mitigating the associated risks. While commodity futures help hedge the price risk but volumetric risks remain largely uncovered. In this paper we have explored various types of weather derivatives that can be used to manage such risks. The article suggests that how weather-based derivative contract system can be used for managing the volume-related weather risk in agriculture sector. Such a contract system needs a reliable rainfall index. In this study, the use of weighted rainfall index and its use for weather derivatives is suggested. Various weather derivative contracts are explored and their utility in managing crop specific risk profiles is suggested. Various models exist for pricing of weather options. Some of the commonly used methods are explored. In the final section, the present state of weather market in India and prerequisites for developing a reliable weather derivates market is discussed.